SUPPLY CHAIN RISK ANALYSIS IN KUB – IK MATARAM MACOA WITH HOUSE OF RISK (HOR) - Ahmad Padhil; Nurul Chairany; Arfandi Ahmad; Hardianti Ramli; Rahmaniah Malik; Anis saleh (Center for Study and Journal Management FTI UMI, 2021)
(KUB - IK ) Mataram Macoa is a cocoa industry . The cocoa industry can produce chocolate with a cocoa material capacity of 87 kg per month or 1.0444 tons per year. Based on data from the Polewali Mandar Regency Statistics Agency, in 2018 the chocolate industry has a prospect that is still less proven with the data from BPS Polewali Mandar Regency, there is only 1 group of cocoa industry centers and the number of business units is 1 unit (BPS Polewali Mandar Regency, 2018).The company does not currently have a structured risk management to identify and mitigate risks that occur, especially in the supply chain function. By using the House of Risk method, the risks that may arise and their causes can be identified to simultaneously find ways to mitigate these risks to improve the operational quality of the Kelompok Usaha Bersama Industri Kecil Mataram Macoa and open opportunities to detect profitable business opportunities for the company. The purpose of this paper is to determine the causes of the dominant risk and design response measures in the Kelompok Usaha Bersama Industri Kecil Mataram Macoa. The basic method of writing is descriptive method and is implemented by using a case study method through a quantitative approach. The selection of respondents was carried out using purposive sampling technique. Methods of data collection by observation, in-depth interviews, questionnaires and literature study. The results of this paper indicate that in the activity plan there are 2 risks, in source activity there are 5 risks, in make activities there are 5 risks, in delievery activities there are 3 risks, and in return activities there is 1 risk. The risk treatment plan is designed to reduce the risk status for each risk event using a risk matrix